PEMBERONTAKAN KESATUAN RAKJAT JANG TERTINDAS (KRJT) DI KALIMANTAN SELATAN (1950-1963): SEBUAH KAJIAN AWAL - Iqbal, Muhammad (Khazanah: Jurnal Studi Islam dan Humaniora, 2018)
The focus of this article is historiography of rebellion of Unity of the Oppressed (Kesatuan Rakjat jang Tertindas/KRjT) which is led by Ibnu Hadjar on South Kalimantan (1950-1963). In 1950, Ibnu Hadjar’s troops choose desertion from Indonesian National Army (Tentara Nasional Indonesia) and entered to the forest on the range of Meratus hills, for doing the rebellion to the Government of Indonesia, whereas, 1963 is the time when The KRjT surrendered and Ibnu Hadjar be arrested. The result showed that the emergence of  KRjT  caused by crystallizing of dissatisfaction and hurt over Jakarta’s policy in treating local ex-guerrillas in the early 1950s. Ibnu Hadjar and his followers felt leisureliness that appear between what they expect in terms of status and  material acquisition with what they have or their capacity for got it (relative deprivation).